Bacteriophage T4 Head: Structure, Assembly, and Genome Packaging - Venigalla B. Rao; Andrei Fokine; Qianglin Fang; Qianqian Shao (Viruses, 2023)
Bacteriophage (phage) T4 has served as an extraordinary model to elucidate biological structures and mechanisms. Recent discoveries on the T4 head (capsid) structure, portal vertex, and genome packaging add a significant body of new literature to phage biology. Head structures in unexpanded and expanded conformations show dramatic domain movements, structural remodeling, and a ~70% increase in inner volume while creating high-affinity binding sites for the outer decoration proteins Soc and Hoc. Small changes in intercapsomer interactions modulate angles between capsomer planes, leading to profound alterations in head length. The in situ cryo-EM structure of the symmetry-mismatched portal vertex shows the remarkable structural morphing of local regions of the portal protein, allowing similar interactions with the capsid protein in different structural environments. Conformational changes in these interactions trigger the structural remodeling of capsid protein subunits surrounding the portal vertex, which propagate as a wave of expansion throughout the capsid. A second symmetry mismatch is created when a pentameric packaging motor assembles at the outer “clip” domains of the dodecameric portal vertex. The single-molecule dynamics of the packaging machine suggests a continuous burst mechanism in which the motor subunits adjusted to the shape of the DNA fire ATP hydrolysis, generating speeds as high as 2000 bp/s.